2021
DOI: 10.1371/journal.pgen.1009539
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the degradation pathway of a disease-linked aspartoacylase variant

Abstract: Canavan disease is a severe progressive neurodegenerative disorder that is characterized by swelling and spongy degeneration of brain white matter. The disease is genetically linked to polymorphisms in the aspartoacylase (ASPA) gene, including the substitution C152W. ASPA C152W is associated with greatly reduced protein levels in cells, yet biophysical experiments suggest a wild-type like thermal stability. Here, we use ASPA C152W as a model to investigate the degradation pathway of a disease-causing protein v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 88 publications
0
22
2
Order By: Relevance
“…Our simple, but accurate prediction algorithm to identify degrons from sequence may help understand the complex relationship between sequence variation and abundance. We and others have previously shown that many disease-causing missense variants are thermodynamically destabilized (Abildgaard et al, 2019; Casadio et al, 2011; Gersing et al, 2021; Kampmeyer et al, 2022; Matreyek et al, 2018; Pey et al, 2003; Stein et al, 2019; Yue et al, 2005). The results presented here provide a key missing part of the puzzle, namely a quantitative model for which exposed sequences are PQC targets, and we hope our work may help develop quantitative models that combine protein stability and recognition via the PQC.…”
Section: Discussionmentioning
confidence: 99%
“…Our simple, but accurate prediction algorithm to identify degrons from sequence may help understand the complex relationship between sequence variation and abundance. We and others have previously shown that many disease-causing missense variants are thermodynamically destabilized (Abildgaard et al, 2019; Casadio et al, 2011; Gersing et al, 2021; Kampmeyer et al, 2022; Matreyek et al, 2018; Pey et al, 2003; Stein et al, 2019; Yue et al, 2005). The results presented here provide a key missing part of the puzzle, namely a quantitative model for which exposed sequences are PQC targets, and we hope our work may help develop quantitative models that combine protein stability and recognition via the PQC.…”
Section: Discussionmentioning
confidence: 99%
“…For Ubr1, a direct interaction with Hsp70 has been observed (Summers et al, 2013), indicating that some PQC E3s may delegate substrate recognition to the chaperones. Similarly, the human CHIP E3 directly interacts with Hsp70 and Hsp90 chaperones to ubiquitylate bound protein substrates (Höhfeld and Jentsch, 1997), while the chaperone NEFs BAG1 and Hsp110 mediate the release of bound substrates at the 26S proteasome (Abildgaard et al, 2020; Gersing et al, 2021; Höhfeld and Jentsch, 1997; Kandasamy and Andréasson, 2018; Kriegenburg et al, 2014). The broad substrate specificity of Hsp70 and its involvement in protein degradation suggest that it plays a fundamental and direct role in targeting misfolded proteins to the UPS via binding their short PQC degrons.…”
Section: Introductionmentioning
confidence: 99%
“…ASPA is predominantly expressed in mature OLs where it functions as a homodimer cleave NAA, releasing acetate that can be used for myelin lipid synthesis (Baslow, et al, 1999;Moore, et al, 2003;Jolly, et al, 2016). The lack of ASPA activity results in the accumulation of NAA and is tightly linked to the Canavan disease, which is a fatal neurodegenerative disorder genetically linked to polymorphisms in the ASPA gene such as substitution C152W (Gersing, et al, 2021;Madhavarao, et al, 2005). OLs' list of known functions extends beyond axon myelination and now includes the direct modulation of neuronal function (de Hoz and Simons 2015; Jha and Morrison 2020).…”
Section: Discussionmentioning
confidence: 99%